Iterative mollifier‐based despiking of the single‐scan Raman spectra - Korepanov, Vitaly (Journal of Raman spectroscopy, 2022)
Removing cosmic spikes from experimental Raman spectra is highly important for the processing of big datasets. The despiking approaches are at present under active development. Herein, an algorithm is described that can handle the single‐scan spectra and works efficiently for both regular and apodized spectra. It is based on an iterative detection–fitting–subtraction cycle, in which the detection is based on a mollification operation. The approach does not require setting arbitrary threshold parameters for the detection. The efficiency of the algorithm is compared with the state‐of‐the‐art approaches. It is shown that it can remove the spikes at which fails the built‐in device software. The Python code is provided. Mollifier‐based algorithm can detect and subtract even minor spikes missed by the built‐in device software.